Evaluation of the effect of hedgerow intercropping using Leucaena leucocephala and fertilizer application on growth and yield of garden eggs (Solanum melongena) (Journal of Science and Technology, 2016)
Field trials were conducted in Ghana to assess the effect of applying Leucaena prunings as mulch and N.P.K., 15-15-15 compound fertilizer on the growth and yield of garden eggs (Solanum melongena) during the 1993 minor and 1994 major cropping seasons. The crop was grown with or without Leucaena mulch as well as 0 kg/ha, 180 kg/ha and 360 kg/ha rates of fertilizer. The crop responded very well to the 15-15-15 compound fertilizer used, since plants without fertilizer had significantly reduced height; more days to flowering, fruiting and harvesting and produced yields far below the potential yield levels of the crop. In both seasons, applying the Leucaena mulch increased the mean yield by 21 percent over the no mulch treatments. Economic analysis of the various treatments showed that: producing the crop during the minor season with rainfall was not profitable; producing the crop during the major season was profitable when the half rate of fertilizer, mulched (F1M1 ); full rate fertilizer, mulched (F2 M1 ) and full rate fertilizer no mulch (F2 M0 ) treatments were applied, with the F1M1 ranking first as the most profitable option. This was shown by the comparative net income per hectare of: ¢1,215,000, ¢1,201,020 and ¢819,020 for the (F1M1 ), (F2M1 ) and (F2M0 ) respectively. Producing garden eggs with Leucaena mulch in hedgerow intercropping could reduce fertilizer requirement, at least by half. Hedgerow intercropping with garden eggs is therefore profitable and may become an attractive alternative to small-scale farmers as prices of inorganic fertilizer continue to increase over the years.